LOVE AND POWER IN THE NOVEL OF THE SABDA PALON: PUDARNYA SURYA MAJAPAHIT BY DAMAR SHASHANGKA. - Rosa, Silvia; Fatma, Surya Dewi (ATAVISME, 2020)
The love and power represented in the novel Sabda Palon: Pudarnya Surya Majapahit is an interesting theme to be discussed semiotics. A series of signs are scattered in this novel to concretize it's meaning and store information related to the factors causing the decline of the Majapahit kingdom. This article discusses the meaning of a series of markers that contain meaning related to the past history of the Majapahit kingdom. The method used is a semiotic method with the presentation of results in the form of descriptive-analytical exposures. The results obtained show that the Sabda Palon: Pudarnya Surya Majapahit revealed unpublished events to the public surface so far, especially related to the romance problem that struck the kingdom's leader, Bhre Kertabhumi with a Chinese princess named Siu Ban Ci, who almost ended the status of Dewi Ambarawati (Princess of Champa) as the official consort of kings in the kingdom. This research concludes that if a love relationship is not controlled properly it can destroy a power. Sabda Palon: Pudarnya Surya Majapahit conveyed the message and the mandate perfectly.